A Comprehensive Bibliometric Analysis of Distance Learning Assessments: Key Themes and Future Directions - Cahyani, Vika Puji; Romadin, Achmad (International Journal of Integrative Sciences, 2024)
Distance learning has become increasingly relevant, mainly fuelled by advances in information and communication technology (ICT) and emergency situations such as the COVID-19 pandemic. Innovations in assessment and evaluation methods are key to improving the quality of education in the context of distance learning. This study aims to identify, analyse and map the main themes and provide recommendations for new directions for future research related to distance learning assessment. This research is quantitative-descriptive in nature using bibliometric analysis techniques. Bibliographic data was taken from a credible scientific database on the Scopus database in the range of 2020-2024 using the keyword ‘Assessment for distance learning’. The data obtained was analysed and the relationship between keywords was mapped. Based on the results of the analysis it can be concluded that the 10 major themes and research trends related to distance learning assessment include distance learning (131), higher education (43), e-learning (40), distance education (34), Covid-19 (30), assessment (24), pandemic (23), blended learning (17), online assessment (16), online education (15). The results of this study can provide a framework for understanding distance learning assessment in a broader and cross-disciplinary context